2022
DOI: 10.1029/2022gl099925
|View full text |Cite
|
Sign up to set email alerts
|

Recent Increase in the Occurrence of Snow Droughts Followed by Extreme Heatwaves in a Warmer World

Abstract: The compound of late winter snow droughts and early spring heatwaves (compound snow drought and heatwave (CSDHW)) could dramatically affect ecosystems and water availability, but has not been systematically investigated. Here we present a comprehensive assessment of CSDHW events and possible driving mechanisms. We find that 7% of the snow‐covered area experiences significant (p < 0.05) CSDHW events, and an average of 35% of snow droughts are followed by heatwaves during 1981–2020. The spatial extent of CSDHW i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The past decade has witnessed a number of rare heavy rainfall events in many countries leading to catastrophic flooding or landslides, as exemplified by recent events in Zhengzhou, China (Yin et al., 2022), New York, USA (The Washington Post, 2021), western Germany (Reuters, 2021), Milan Malpensa Airport, Italy (Wanted in Milan, 2021), and Singapore (FloodList, 2021). Zhengzhou was hit by massive flooding on 20 July 2021 due to an unprecedented 622.7 mm of rain that fell in 24 hr, which led to 292 known deaths and affected more than 11 million people, despite having invested over $80 million since 2016 in upgrading urban infrastructure (Li & Wang, 2022; Yin et al., 2022). The intensity and frequency of heavy rainfall events are expected to increase under a warming climate, as highlighted in recent studies and the Sixth Assessment Report of the Intergovernmental Panel on Climate Change (Qing et al., 2022; Seneviratne et al., 2021; Zhu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has witnessed a number of rare heavy rainfall events in many countries leading to catastrophic flooding or landslides, as exemplified by recent events in Zhengzhou, China (Yin et al., 2022), New York, USA (The Washington Post, 2021), western Germany (Reuters, 2021), Milan Malpensa Airport, Italy (Wanted in Milan, 2021), and Singapore (FloodList, 2021). Zhengzhou was hit by massive flooding on 20 July 2021 due to an unprecedented 622.7 mm of rain that fell in 24 hr, which led to 292 known deaths and affected more than 11 million people, despite having invested over $80 million since 2016 in upgrading urban infrastructure (Li & Wang, 2022; Yin et al., 2022). The intensity and frequency of heavy rainfall events are expected to increase under a warming climate, as highlighted in recent studies and the Sixth Assessment Report of the Intergovernmental Panel on Climate Change (Qing et al., 2022; Seneviratne et al., 2021; Zhu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The total inundation areas would increase to up to 10,200 square meters by 2100, which is comparable with those induced by Typhoon Mangkhut and Hato. It should be noted that such an inundation projection is solely based on the mean sea level and the risks would further increase if the projected extreme sea level was taken into account [41][42][43][44][45][46][47][48][49][50][51].…”
Section: Projection Of Coastal Floodingmentioning
confidence: 99%
“…Moreover, changing sowing dates of major crops (corn and soybean) cause crop biomass and yield fluctuations (Abendroth et al, 2017;Baum et al, 2019;Lou et al, 2021). Li and Wang (2022) found that 35% of snow droughts were followed by heatwaves during 1981-2020. These snow impact studies show that snow-related analysis need to be conducted in different vulnerable basins and shared using watershed information systems for planning and management (Demir and Beck, 2009).…”
Section: Introductionmentioning
confidence: 99%